Pesticides and food safety: An assessment of the Pre-Harvest Interval compliance in cabbage cultivation (Brassica oleracea L. var. capitata) in Nicaragua - Rodríguez-Salguera, Víctor Hugo (2025)
Introduction. Pesticides are essential tools in agricultural production. In crops like cabbage, their intensive use requires identifying the active ingredients (AIs) applied and evaluating their implications for consumer’s health. One critical agronomic criterion is the pre-harvest interval (PHI), which ensures that pesticide residues dissipate to safe levels before harvest. Objective. To identify the main AIs used in pest management of cabbage crops in Nicaragua and assess compliance with the PHI stablished by manufacturers. Materials and methods. Seventy-nine surveys were conducted, in physical format and using the KoboCollect mobile application to gather data on pesticide use. The AIs were verified using international databases such as the Pesticide Properties Database. Additionally, twenty pesticide application record books were collected from producers to analyze PHI compliance. A snowball and convenience sampling strategy were employed. Results. A total of 74 AIs were identified through surveys, including insecticides (42%), fungicides (38%), fungicide-bactericides (12%), and herbicides (8%). The most frequently used AIs were profenofos, carbendazim, copper sulfate pentahydrate, and glyphosate. From the record books, 52 AIs were documented across 330 pesticide applications. Among these, 36% of AIs and 16% of applications did not comply with the PHI. Furthermore, 39% of producers failed to meet this criterion in at least one application. The use of non-authorized AIs for cabbage and the lack of awareness regarding PHI were notable findings. Conclusion. The use of unauthorized or hazardous AIs and the lack of PHI fulfillment represent a significant risk to public health. These findings highlight the urgent need for regulatory oversight and educational interventions to promote safe pesticide use in cabbage production systems.